PENGARUH SENYAWA KOFAKTOR DAN STABILITAS TERHADAP AKTIVITAS ENZIM β-1,3-GLUKANASE DARI ISOLAT BAKTERI TERMOFIL Bacillus licheniformis HSA3-1a - Seniwati Dali; Hasnah Natsir; Gusti Gusti (As-Syifaa Jurnal Farmasi, 2012)
Study on the effect of compound cofactor and stability to enzyme activity of β-1 ,3-glucanase has been done. This study used bacterial isolates B. licheniformis HSA3-1a isolated from a hot spring Sulili Pinrang as a source of the enzyme β-1 ,3-glucanase. Isolation of enzyme made after bacterial are activated and cultured in fermentation medium, pH 7,0 and temperature of 50 0C for 4 days. The resulting enzyme performed activity assay. Activity of enzyme assays performed by adding the compound cofactor MgCl2, CaCl2, CuCl2, CoCl2, and ZnCl2 at different concentrations (0.25, 0.5, and 1.0) mM. To determine the stability of the enzyme made by varying the incubation time (0, 30, 60, 90, 120 and 180) minutes. The result showed that the cofactors of compounds that can serve as an activator for the enzyme β-1 ,3-glucanase from B. licheniformis HSA3-1a is MgCl2 and CaCl2 at a concentration of 0:25 mM, 0.5 mM and 1.0 mM. Compound cofactor of CaCl2 1 mM is stabilizier of enzyme β-1,3-glukanase because the relative activity of the enzyme remaining 86% of the treatment time for 180 minutes prainkubasi.Key Word : β-1 ,3-glucanase, Bacillus  licheniformis HSA3-1a, cofactor, enzyme activity, stability